2009
DOI: 10.1021/jp809735e
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Modes of the Vinyl and Deuterated Vinyl Radicals

Abstract: Following the initial report of the detection of fundamental transitions of all nine vibrational modes of the vinyl radical [Letendre , L. ; Liu , D.-K. ; Pibel , C. D. ; Halpern , J. B. ; Dai , H.-L. J. Chem. Phys. 2000 , 112 , 9209] by time-resolved IR emission spectroscopy, we have re-examined the assignments of the vibrational modes through isotope substitution. Precursor molecules vinyl chloride-d3, vinyl bromide-d3, and 1,3-butadiene-d6 are used for generating vibrationally excited vinyl-d3 through 193 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 76 publications
3
49
1
Order By: Relevance
“…During the past decades, this species has been extensively characterized by various spectroscopic techniques, both in the gas and solid phases. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The experimental studies have provided basic knowledge of the structure and vibrational spectra of vinyl radicals, which is in agreement with the state-of-the-art calculations. [15][16][17] Noncovalent interactions play an important role in many chemical, physical, and biological processes.…”
Section: Introductionsupporting
confidence: 68%
“…During the past decades, this species has been extensively characterized by various spectroscopic techniques, both in the gas and solid phases. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The experimental studies have provided basic knowledge of the structure and vibrational spectra of vinyl radicals, which is in agreement with the state-of-the-art calculations. [15][16][17] Noncovalent interactions play an important role in many chemical, physical, and biological processes.…”
Section: Introductionsupporting
confidence: 68%
“…Concerning particularly difficult analyzes of experimental spectra of free radicals, it has already been shown (e.g., for the F 2 NO 20 or vinyl 18,121,122 radicals) that accurate computational studies can lead to correction of the vibrational frequencies assignment. Actually, for the vinyl radical the discrepancies observed between the computed and experimental gas-phase infrared spectrum 123 led to an experimental re-investigation, 124 which in turn confirmed the theoretical predictions. In this frame, it is suggested that the 1400-1600 cm −1 spectral zone of C 6 H 5 , where bands due to precursor and water impurities are clearly present as well as the assignment of υ 23 of C 6 D 5 should be re-investigated with the help of fully anharmonic IR and/or Raman simulated spectra, also accounting for the species possibly present in the experimental mixture and, in case, including a few sets of isotopically substituted precursors.…”
Section: Resultsmentioning
confidence: 71%
“…The details of our time-resolved Fourier transform infrared (TR-FTIR) emission spectroscopy experiment have been described previously [31,32], and are reviewed in the Supplemental Material. Briefly, a mixture of SO 2 , hydrogen bromide (HBr), and argon (Ar) gas is continuously flowed through a reaction cell, and irradiated with 193 nm pulses from an ArF excimer laser.…”
mentioning
confidence: 99%